2006
DOI: 10.1073/pnas.0603152103
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Asian wild rice, Oryza rufipogon , reveals multiple independent domestications of cultivated rice, Oryza sativa

Abstract: Cultivated rice, Oryza sativa L., represents the world's most important staple food crop, feeding more than half of the human population. Despite this essential role in world agriculture, the history of cultivated rice's domestication from its wild ancestor, Oryza rufipogon, remains unclear. In this study, DNA sequence variation in three gene regions is examined in a phylogeographic approach to investigate the domestication of cultivated rice. Results indicate that India and Indochina may represent the ancestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
466
2
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(508 citation statements)
references
References 37 publications
22
466
2
7
Order By: Relevance
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
“…A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wild rice was first domesticated in the Yangtze region of China to 2 cultivated subspecies, indica and japonica [1]. Phylogeographic investigations have suggested that cultivated rice has experienced at least two independent domestications: indica rice was domesticated within a region south of the Himalaya mountains whereas japonica was domesticated from wild rice in southern China [2]. Many ancient rice remains have been found in China, such as in Hemudu in Zhejiang Province, Lixian in Hunan Province, and Jiahu in Henan Province [3].…”
mentioning
confidence: 99%
“…More than 90% of the world's rice is grown and consumed in Asia, where 60% of the earth's people live. Rice is also one of the major staple foods in China, a center of origin of Asian cultivated rice (Khush 1997, Londo et al 2006. The production of japonica rice in northern China is famous for its higher yield and good quality and accounts for 50% of the total production.…”
Section: Introductionmentioning
confidence: 99%